HUBUNGAN PENGETAHUAN DAN SELF EFFICACY DENGAN MOTIVASI PASIEN HIPERTENSI UNTUK MELAKUKAN PEMERIKSAAN TEKANAN DARAH - Ester, Ester; Rusdi, Rusdi (JURNAL KESEHATAN KARTIKA, 2026)
Background: The global prevalence of hypertension is on the rise. This lack of motivation is exacerbated by minimal support from the surrounding community and a healthcare system that is not yet optimal in facilitating routine monitoring. Regular blood pressure checks are key to the early detection and management of hypertension. Objective: To identify the relationship between knowledge and self-efficacy and the motivation of hypertensive patients to have their blood pressure checked at community health centers. Methods: A descriptive study of 50 hypertensive patients selected using total sampling; data were collected via a questionnaire and analyzed using the Chi-Square test. Results: Respondents were adults (90%), predominantly female (70%), married (86%), with an education level of ≤ elementary school (30%), and farmers (63%). Knowledge was moderate (78%), self-efficacy was high (62%), and motivation was high (76%). All those with high knowledge had high motivation (p > 0.05), whereas 94.7% of those with high self-efficacy had high motivation (p < 0.05). Conclusion: There is no association between knowledge and patient motivation to measure blood pressure; however, there is a significant association between self-efficacy and patient motivation to measure blood pressure at the community health center. It is recommended to enhance educational programs and provide ongoing support to strengthen the knowledge, self-efficacy, and motivation of hypertensive patients regarding routine blood pressure monitoring.